PENGARUH CITRA MEREK DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS KONSUMEN PADA METRO ELEKTRONIK DAN FURNITURE CASH DAN KREDIT KOTA SUNGAI PENUH - Zefri Efdison (Institut Agama Islam Negeri Kerinci, 2021)
Purpose: This study has the aim and intent to test whether brand image and consumer satisfaction are able to predict changes in consumer loyalty of Metro Eloktronik and Furniture Cash and Credit. Design/Methodology/Approach: This study applies a quantitative approach to answer the research hypothesis, therefore this study uses multiple linear regression statistical tests with the help of IBM SPSS.25 application to analyze the collected data. Findings: This study found that the proposed regression model is suitable. However, partially Brand Image has no significant effect on consumer loyalty, while customer satisfaction has a significant effect on consumer loyalty. Research implications: Consumer satisfaction is a factor that can determine consumer loyalty, the more consumers feel satisfied with a product, the loyalty to the product will also increase.